224k views
1 vote
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!!

If f(x) = -3x^4 - 2x^3 + 3x^2, and g(x) = 3x^4 - 4x^3 + x^2 then f(x) + g(x) =

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! If f(x) = -3x^4 - 2x^3 + 3x^2, and-example-1
User Go Minimal
by
5.1k points

1 Answer

5 votes

Answer: B) -6x³ + 4x²

Explanation:

Add like terms:


.\ f(x):\quad -3x^4-2x^3+3x^2\\+g(x):\quad \underline{+3x^4-4x^3+1x^2}\\.\qquad \qquad \qquad \ \ \boxed{-6x^3+4x^2}

User Sherif Ahmed
by
4.9k points